Indirect rapid prototyping of biphasic calcium phosphate scaffolds as bone substitutes: Influence of phase composition, macroporosity and pore geometry on mechanical properties - Detsch, Rainer; et al. (Journal of Materials Science: Materials in Medicine, 2010)
While various materials have been developed for bone substitute and bone tissue engineering applications over the last decades, processing techniques meeting the high demands of scaffold shaping are still under development. Individually adapted and mechanically optimised scaffolds can be derived from calcium phosphate (CaP-) ceramics via rapid prototyping (RP). In this study, porous ceramic scaffolds with a periodic pattern of interconnecting pores were prepared from hydroxyapatite, β- tricalcium phosphate and biphasic calcium phosphates using a negative-mould RP technique. Moulds predetermining various pore patterns (round and square cross section, perpendicular and 60° inclined orientation) were manufactured via a wax printer and subsequently impregnated with CaP-ceramic slurries. Different pore patterns resulted in macroporosity values ranging from about 26.0-71.9 vol% with pore diameters of approximately 340 μm. Compressive strength of the specimens (1.3-27.6 MPa) was found to be mainly influenced by the phase composition as well as the macroporosity, both exceeding the influence of the pore geometry. A maximum was found for scaffolds with 60 wt% hydroxyapatite and 26.0 vol% open porosity. It has been shown that wax ink-jet printing allows to process CaP-ceramic into scaffolds with highly defined geometry, exhibiting strength values that can be adjusted by phase composition and pore geometry. This strength level is within and above the range of human cancellous bone. Therefore, this technique is well suited to manufacture scaffolds for bone tissue engineering. © Springer Science+Business Media, LLC 2010.